Entrainment and Synchronization to Auditory Stimuli During Walking in Healthy and Neurological Populations: A Methodological Systematic Review - Moumdjian, Lousin; Buhmann, Jeska; Willems, Iris; Feys, Peter; Leman, Marc (Frontiers in Human Neuroscience, 2018)
Background. Interdisciplinary work is needed for scientific progress, and with this review, our interest is in the scientific progress towards understanding the underlying mechanisms of auditory-motor coupling, and how this can be applied to gait rehabilitation. Specifically we look into the process of entrainment and synchronisation; where entrainment is the process that governs the dynamic alignments of the auditory and motor domains based on error-prediction correction, whereas synchronisation is the stable maintenance of timing during auditory-motor alignment. Methodology. A systematic literature search in databases PubMed and Web of Science were searched up to 9th of Aug 2017. The selection criteria for the included studies were adult populations, with a minimum of five participants, investigating walking to an auditory stimulus, with an outcome measure of entrainment and synchronisation. The review was registered in PROSPERO as CRD42017080325. Objectives. The objective of the review is to systematically describe the metrics which measure entrainment and synchronisation to auditory stimuli during walking in healthy and neurological populations. Results. Sixteen articles were included. 50% of the included articles had healthy controls as participants (N = 167), 19% had neurological diseases such as Huntington’s and Stroke (N = 76) and 31% included both healthy and neurological (Parkinson’s disease and Stroke) participants (N = 101). In the included studies, six parameters were found to capture the interaction between the human movement and the auditory stimuli, these were: cadence, relative phase angle, resultant vector length, interval between the beat and the foot contact, period matching performance and detrended fluctuation analysis. Conclusion. In this systematic review, several metrics have been identified, which measure the timing aspect of auditory-motor coupling and synchronisation of auditory stimuli in healthy and neurological populations during walking. The application of these metrics may enhance the current state of the art and practice across the neurological gait rehabilitation. These metrics also have current shortcomings. Of particular pertinence is our recommendation to consider variability in data from a time-series rather than time-windowed viewpoint. We need it in view of the promising practical applications from which the studied populations may highly benefit in view of personalized medical care.